Cellular injury in liver diseases - Ding, Wen-Xing; Yin, Xiao-Ming (Springer, 2017)
This comprehensive volume describes drug and virus-mediated hepatocyte injury, alcohol, lipid and bile acid-induced hepatocyte injury in addition to ischemia-reperfusion-mediated liver injury. The chapter authors who discuss these topics are leading experts on cell death in liver diseases. The authors link these different types of liver injury to the commonly associated liver inflammation, fibrosis and tumorigenesis. Other topics explored include the various forms of cell death and cell survival pathways that have been identified in the liver, such as apoptosis, necroptosis, pryoptosis and autophagy. This book, along with its companion volume, Molecules, Systems and Signaling in Hepatic Cell Death, provides a thorough and comprehensive discussion on the topic of cell death and liver disease. Cellular Injury in Liver Diseases is an essential addition to the Cell Death in Biology and Diseases series and will appeal to scientists, clinicians and those doing research for drug discovery.
Keywords: Liver -- Diseases -- Molecular aspects.; Cell death.; elektronické knihy; electronic books